A study of the effects of trypanosome infection on the fertility of female goats in Lulangwa Valley, eastern Zambia - Perry, Brian D.; Chamboko, Tafireyi; Mahan, S.; Medley, G.F.; Mukhebi, A.W.; O'Callaghan, C.J.; Peter, T.F. (OAU/STRC, 1995)
Seventy 1- to 4-year old female indigenous goats were matched and randomised into two groups to measure the effects of naturally acquired trypanosome infections on oestrus and conception. All goats were treated twice with diminazene aceturate (Berenil) at 7 mg/kg body weight at two-week intervals. Two and six weeks later 28 goats received 0.5 mg/kg of isometamidium chloride (Samorin): Forty-two goats were not treated during this period. A male goat was then introduced to both groups for three weeks. Following removal of the male goat all 70 female goats were treated with Berenil and subsequently protected with Samorin until kidding. Goats were sampled weekly. During the six weeks before and the three weeks when the male was with the females, 15 of the 42 unprotected goats were detected parasitaemic on at least one occasion. No parasitaemias were detected among the 28 protected goats. Twenty three of the 28 (82 percent) protected goats kidded successfully compared to 23 of the 42 (55 percent) unprotected goats.